Open Dialogue in Spain: an initial survey of knowledge and perspectives - Parrabera-García, Silvia; Oujo-Fernández, Casilda; Lirola, María-Jesús; Cangas, Adolfo J.; Marfá-Vallverdú, Jordi; Correa-Urquiza, Martín; Garcia-Torrents, Enric (Frontiers in Psychology, 2023)
In Spain, the introduction of the Open Dialogue framework is relatively recent. This study takes a closer look at Open Dialogue training, interest and research in this region. To this end, a survey has been conducted through a convenience sample of professionals, people with their own experiences in mental health, family members, relatives, university professors and students. The results showed that a significant number of participants had no training in OD, and their exposure to relevant literature and congress attendance was limited. Amongst the different profiles, professionals reported the highest level of training. These findings highlight the urgent need for further research and training initiatives to improve the understanding and application of the OD framework in Spain. Efforts should be directed towards broadening the knowledge base, increasing access to training programmes and fostering interest amongst different stakeholders. By addressing these gaps, the implementation and use of OD can be expanded to meet the growing demand and interest in this approach in the Spanish context.